2006
DOI: 10.1111/j.1440-1673.2006.01545.x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative ultrasound‐guided fine‐needle aspiration cytology for axillary staging in breast carcinoma

Abstract: Axillary lymph node (ALN) status is considered to be the single most important prognostic indicator in patients with breast cancer. It can be assessed by various radiological, pathological and surgical techniques, the most accurate being histological examination of lymph nodes after axillary lymph node dissection (ALND). This prospective study was conducted to assess the feasibility and diagnostic accuracy of preoperative ultrasound (US) and ultrasound-guided fine-needle aspiration cytology (USG-FNAC) of ALN i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0
5

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 17 publications
3
55
0
5
Order By: Relevance
“…The difference in the sensitivity of the FNA in the sentinel lymph node group compared with the full lymph node dissection group relates to the small size of the metastatic foci in the sentinel lymph node group, decreasing the likelihood of sampling the metastatic foci. Other studies have also shown that the most common cause of false-negative cases is inadequate sampling, 11 either because of the small size of the metastases, 1,3,7 the low number of lymph nodes positive for metastasis, 1,3,19 or failure to observe the lymph nodes during examination of the axilla by ultrasound. 1,3,18,19 Reported causes of false-positive diagnoses in the literature are due mostly to cytologic misinterpretation of cells 11 or inadequate sampling of the lymph node dissection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The difference in the sensitivity of the FNA in the sentinel lymph node group compared with the full lymph node dissection group relates to the small size of the metastatic foci in the sentinel lymph node group, decreasing the likelihood of sampling the metastatic foci. Other studies have also shown that the most common cause of false-negative cases is inadequate sampling, 11 either because of the small size of the metastases, 1,3,7 the low number of lymph nodes positive for metastasis, 1,3,19 or failure to observe the lymph nodes during examination of the axilla by ultrasound. 1,3,18,19 Reported causes of false-positive diagnoses in the literature are due mostly to cytologic misinterpretation of cells 11 or inadequate sampling of the lymph node dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also shown that the most common cause of false-negative cases is inadequate sampling, 11 either because of the small size of the metastases, 1,3,7 the low number of lymph nodes positive for metastasis, 1,3,19 or failure to observe the lymph nodes during examination of the axilla by ultrasound. 1,3,18,19 Reported causes of false-positive diagnoses in the literature are due mostly to cytologic misinterpretation of cells 11 or inadequate sampling of the lymph node dissection. 19 In the current study, there were no false-positive FNA cases; indeed, although 1 FNA specimen diagnosed as metastatic breast carcinoma was not confirmed histologically (all of the 28 lymph nodes resected were found to be negative), review of the FNA smears and cell block material demonstrated unequivocally malignant cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, 44 articles included information relating FNAC and breast cancer diagnosis. But only 21 of 44 articles satisfied the requirements of the meta-analysis fully (Bonnema et al, 1997;Bedrosian et al, 2003;Deurloo et al, 2003;Kuenen-Boumeester et al, 2003;Sapino et al, 2003;Duchesne et al, 2005;Podkrajsek et al, 2005;Popli et al, 2006;van Rijk et al, 2006;Altomare et al, 2007;Ciatto et al, 2007;Alkuwari et al, 2008;Tahir et al, 2008;Baruah et al, 2010;Jung et al, 2010;Luparia et al, 2010;Carroll et al, 2011;Devaraj et al, 2011;Hayes et al, 2011;Schiettecatte et al, 2011), addressing the value of FNAC in staging of axillary lymph node in breast cancer patients. The detailed procedure was seen in Figure 1.…”
Section: Literature Search and Selectionmentioning
confidence: 99%